Sarcopenia and Fall Risk Among Community-Dwelling Older Adults in Indonesia: A Cross-Sectional Analysis - Ashar Prima; Fuji Fauzi; Indah Puspitasari; Maratun Shoaliha; Fauziah H. Wada; Amzal Mortin Andas (Direktorat Politeknik Kesehatan Makassar, 2026)
Sarcopenia and falls are major geriatric syndromes that significantly impact functional independence, mobility, and overall health status among older adults. As the aging population continues to increase, understanding the physiological, functional, and environmental links between muscle deterioration and fall vulnerability becomes essential for effective community-based health management. This study aimed to analyze the association between sarcopenia risk and fall risk among community-dwelling older adults in the Wanasari Cibitung area of Bekasi, Indonesia. A cross-sectional study was conducted with 305 older adults aged 60 years and above selected using consecutive sampling. Sarcopenia risk was assessed using the SARC-CalF tool, which combines the SARC-F questionnaire with calf circumference measurement, while fall risk was evaluated using the P3G assessment consisting of 11 fall-related domains. Sociodemographic data, chronic disease profiles, and physical function indicators were collected through structured interviews and standardized measurements performed by trained enumerators. Data analysis included descriptive statistics to determine prevalence and Spearman’s rank correlation to examine the relationship between sarcopenia and fall risk due to non-normal data distribution. Findings revealed that 44.9% of respondents were categorized as high risk for sarcopenia, and 55.4% were classified as high risk for falling. The mean SARC-CalF score was 6.70 ± 6.15, and the mean P3G score was 5.60 ± 4.84, indicating substantial muscle function decline and fall susceptibility within the population. A strong positive correlation was identified between sarcopenia and fall risk (r = 0.612; p < 0.001; 95% CI; 0.53-0.68) ), demonstrating that higher sarcopenia severity is associated with greater fall vulnerability. These results highlight the urgent need to integrate sarcopenia screening and fall-prevention strategies within routine primary healthcare services for older adults